Análisis financiero a la cooperativa de ahorro y crédito “Gonzanamá” periodo 2014-2015 y proyección de los estados financieros - Luzón Cuenca, Paúl De Jesús (2016)
The present thesis entitled: FINANCIAL ANALYSIS TO THE "GONZANAMÁ" SAVINGS AND CREDIT COOPERATIVE PERIOD 2014-2015 AND PROJECTION OF THE FINANCIAL STATEMENTS, allowed to know the economic and financial situation of the cooperative. The horizontal analysis method was applied, determining as the most representative items the account banks and other financial institutions, loan portfolio, obligations with the public, interest and interest and loan portfolio discounts. From the horizontal method performed, it was known that the funds available funds, loan portfolio; Obligations with the public decreased significantly with respect to 2014; Nevertheless it increased the patrimony, income and the expenses. The analysis Pearls indicates that the protection indicators are met; Reaches the majority of requirements of the financial structure, except for financial investments, contributions and loan delinquencies. Liquidity requirements are not met; Unproductive assets surpass the established target; While the level of non-performing asset financing is normal; Finally, an increase in the contributions of the partners, institutional capital, number of partners, but decreases the loan portfolio, savings deposits and, consequently, the asset. The projection identified moderate increases in assets, liabilities, equity, income and expenses. Therefore favorable and unfavorable situations were found in the different items of the analyzed financial statements, this served as a basis to suggest the implementation of alternatives that promote a better use of financial resources and achieve the growth of the cooperative and its positioning in the market.